Do minimum wages induce immigration? - Corrado Giulietti (IZA World of Labor, 2015)
An increase in the minimum wage in immigrant destination countries raises the earnings that low-skilled migrants could expect to attain if they were to migrate. While some studies for the US indicate that a higher minimum wage induces immigration, contrasting evidence shows that immigrants are less likely to move into areas with higher or more frequent increases in the minimum wage. These different findings seem to reflect different relocation decisions by immigrants who have lived in the US for several years, who are more likely to move in response to higher minimum wages, and by new immigrants, who are less likely to move.
Keywords: J08; J23; J61; 330; minimum wage; immigration; low-educated workers